Recommendations for effective documentation in regional anesthesia: an expert panel Delphi consensus project. Issue 5 (22nd February 2022) - Ahmed, Hassan M; Atterton, Benjamin P; Crowe, Gillian G; Barratta, Jaime L; Johnson, Mark; Viscusi, Eugene; Adhikary, Sanjib; Albrecht, Eric; Boretsky, Karen; Boublik, Jan; Breslin, Dara S; Byrne, Kelly; et al.
Abstract : Background and objectives: Documentation is important for quality improvement, education, and research. There is currently a lack of recommendations regarding key aspects of documentation in regional anesthesia. The aim of this study was to establish recommendations for documentation in regional anesthesia. Methods: Following the formation of the executive committee and a directed literature review, a long list of potential documentation components was created. A modified Delphi process was then employed to achieve consensus amongst a group of international experts in regional anesthesia. This consisted of 2 rounds of anonymous electronic voting and a final virtual round table discussion with live polling on items not yet excluded or accepted from previous rounds. Progression or exclusion of potential components through the rounds was based on the achievement of strong consensus. Strong consensus was defined as ≥75% agreement and weak consensus as 50%–74% agreement. Results: Seventy-seven collaborators participated in both rounds 1 and 2, while 50 collaborators took part in round 3. In total, experts voted on 83 items and achieved a strong consensus on 51 items, weak consensus on 3 and rejected 29. Conclusion: By means of a modified Delphi process, we have established expert consensus on documentation in regional anesthesia.